Exponential Growth Pattern of Consumer Well-Being and Attractiveness of Tourism Digital Destination - Albert Hasudungan; Eka Ardianto; Redha Widarsyah (Journal of Economics, Business, and Accountancy Ventura, 2021)
This research aims to explore the connective patterns of 7 dimensions of tourism consumer well-being (environmental altruism, spiritual attunement, inspirational mindfulness, bio-psychological aspect, entrepreneurship, social connectedness, and cultural identity) to induce more tourism growth attractiveness in visiting the digital destination of the My Trip My Adventure (MTMA) Labuan Bajo YouTube platform. The study stems from a postmodern approach where the virtual world and reality are eroded in digital technology development. This study enriches that postmodern perspective by elaborating on 7 dimensions of tourism consumer welfare and the 4 V’s of digital technology innovation (volume, variety, velocity, and veracity). This study collected comments, replies, and ‘like’ expressions on YouTube from October 2016 to October 2019 from the My Trip My Adventure (MTMA) Labuan Bajo YouTube platform. The researchers then analyzed through thematic analysis and social network analysis. This research confirms the polynomial growth pattern from the 7 dimensions of tourism consumer well-being. In general, the pattern goes up from environmental well-being to inspirational mindfulness. Then, it descends to biophysical well-being. It is because to have exponential growth; tourism needs to be absent temporarily. Suddenly after that, the growth goes up in terms of social and cultural well-being. The findings can benefit tourism practitioners in orchestrating their 7 dimensions of tourism consumer well-being as destination orchestrators.